Comprehensive geriatric assessment among elderly people in a convalescence unit: a best practice implementation project. Issue 4 (29th December 2021) - Sianes-Gallén, Mònica; Pujol-García, Anna María; González-Ferrero, Alba; Plaza-Valle, Patricia; Aguilera-Gómez, Ricardo; Canta-López, Elena; Antón-Nieto, Esperanza; González-Ávila, Bárbara; Torrecabota-Gambín, Aroa; Jornet-Gibert, Montsant
ABSTRACT: Aim: The aim of this project was to audit the usual assessment practices employed when admitting patients to a convalescence unit on the outskirts of Barcelona, Spain. The project implemented strategies to improve evidence-based practice using the Joanna Briggs Institute methodology. The specific objectives of this project were (1) to improve completion of the comprehensive geriatric assessment (CGA) record, (2) to improve professionals' CGA knowledge, (3) to promote interdisciplinary work, (4) to improve tailored therapeutic plan generation by implementing evidence-based practice criteria within the instrument, and (5) to evaluate the records and action plans derived from the CGA. Methods: Pre-/post-implementation audit methodology was used the Practical Application of Clinical Evidence System and Getting Research into Practice, and was developed in multiple phases. The implementation phase took 6 months. A sample of 34 consecutive admissions had their CGA patient records evaluated. Descriptive statistics were calculated. Results: A total of 64 records (34 pre/30 post) were reviewed to assess CGA completion. The baseline audit results showed that only two audit criteria were higher than 50%, indicating poor knowledge about the concept of CGA and poor compliance with the current program. Following the implementation of the strategies, which included education and the development of a checklist, there was an improvement in all the criteria audited: the record was correctly completed in 67% of cases, and 80% of team members were knowledgeable and competent in CGA. Conclusion: Several barriers were identified at baseline, and various strategies were implemented to improve CGA compliance. The results show that the project increased awareness of the importance of a comprehensive assessment of the care that patients receive, resulting in better CGA completion.